A Novel Circular RNA hsa_circRPPH1_015 Exerts an Oncogenic Role in Breast Cancer by Impairing miRNA-326-Mediated ELK1 Inhibition - Zhao, Chunming; Li, Linlin; Li, Zhiwei; Xu, Jiawen; Yang, Qing; Shi, Peng; Zhang, Kaining; Jiang, Rui (Frontiers in Oncology, 2020)
Background: Breast cancer (BC) represents a heterogeneous disease with distinct subtypes and high tumor metastatic potentials. Recent researchers identify the implication of circular RNAs (circRNAs) in the initiation of BC. Herein, we uncover a novel circRNA hsa_circRPPH1_015 as a tumor promoter in BC. Methods: A total of 86 paired cancerous and noncancerous tissues were surgically resected and collected from BC patients. Cell proliferation, colony formation, and cell invasion were examined by Edu staining, clone formation assays, propidium iodide (PI)-labeled flow cytometry, and Transwell invasion assays. PCNA, Ki67, MMP-2, MMP-9, Cyclin D1, and CDK4 expression was assayed using Western blot analysis. RNA pull-down, dual-luciferase reporter gene assay, and RNA immunoprecipitation (RIP) assay were performed to investigate the relationships among hsa_circRPPH1_015, microRNA-326 (miRNA-326) and ELK1. The tumor growth of human BC MCF-7 cells in vivo was evaluated in nude mice by subcutaneous xenografts of MCF-7 cells. Results: hsa_circRPPH1_015 expression was upregulated in BC tissues. Knockdown of hsa_circRPPH1_015 restrained the aggreassive behavior of MCF-7. hsa_circRPPH1_015 could bind to miRNA-326 that negatively regulates ELK1. Elevation of miRNA-326 expression resulted in inhibition of cell proliferation, colony formation, and cell invasion of MCF-7. Disturbance of miRNA-326 or overexpression of ELK1 restored the proliferation and agressiveness in hsa_circRPPH1_015-depleted MCF-7 cells. Tumor growth of MCF-7 cells in vivo was reduced in nude mice lack of endogenous hsa_circRPPH1_015 expression. Conclusion: Overall, the present study demonstrates that hsa_circRPPH1_015 was an oncogene and unfavorable prognostic factor in BC, providing an exquisite therapeutic target for BC.